Effects of ball bond diameter on wire bond reliability for automotive application. Issue 1 (4th January 2016) - Peng, Hui Yuen; Devarajan, Mutharasu; Lee, Teik Toon; Lacey, David
Abstract : Purpose: – The purpose of this paper is to investigate the reliability of wire bonds with three varying ball bond diameters, which are ball bonded with three different sizes of gold wires in light-emitting diode (LED) package under high-temperature environment. In automotive applications, "lifted ball bond" issue is a potential critical point for LED device reliability, as the wire bonds are usually stressed under high operating temperature during their lifetime. Moreover, the reliability of wire bonds in recent LED production has fallen under scrutiny due to the practice of reducing wire diameters to cut down production costs. Design/methodology/approach: – Three gold wires with sizes of 2, 1.5 and 1 mm were ball bonded on the LED chip bond pad via thermosonic wire bonding method to produce three different ball bond diameters, that is, 140, 120 and 100 μm, respectively. The reliability of these wire bond samples was then studied by performing isothermal aging at 200°C for the time interval of 30, 100 and 500 hours. To validate hypotheses based on the experimental data, COMSOL Multiphysics simulation was also applied to study the thermal stress distribution of wire bond under an elevated temperature. Findings: – Experimental results show that the interfacial adhesion of wire bond degrades significantly after aging at 200°C for 500 hours, and the rate of interfacial degradation was found to be more rapid in the wire bond with smaller ball bond diameter. Experimental results also show that ball bonds randomly elongate along an axis and deforms into elliptical shapes after isothermal aging, and ball bonds with smaller diameters develop more obvious elongations. This observation has not been reported in any previous studies. Simulation results show that higher thermal stress is induced in the wire bond with the decrease of ball bond diameter. Practical implications: – The reliability study of this paper provides measurements and explanation on the effects of wire diameter downsizing in wire bonds for automotive application. This is applicable as a reliability reference for industries who intend to reduce their production costs. Other than that, the analysis method of thermal stresses using COMSOL Multiphysics simulations can be extended by other COMSOL Multiphysics users in the future. Originality/value: – To resolve "lifted ball bond" issue, optimization of the bond pad surface quality and the wire bond parameter has been studied and reported in many studies, but the influence of ball bond diameter on wire bond reliability is rarely focused. Moreover, the observation of ball bonds randomly elongate and deform more into elliptical shape, and ball bond with smaller diameter has the highest elongation after isothermal aging also still has not been reported in any previous studies.